2020
DOI: 10.1101/2020.04.21.051359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iterative inhibition of commissural growth cone exploration, not post-crossing barrier, ensures forward midline navigation through SlitC-PlxnA1 signaling

Abstract: Sensitization to Slits and Semaphorin (Sema)3B floor plate repellents after midline crossing is thought to be the mechanism expelling commissural axons contralaterally and preventing their back-turning. We studied the role of Slit-C terminal fragment sharing with Sema3B the Plexin (Plxn) A1 receptor, newly implicated in midline guidance. We generated a knock-in mouse strain baring PlxnA1Y1815F mutation altering SlitC but not Sema3B responses and observed recrossing phenotypes. Using fluorescent reporters, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
2
0
0
Order By: Relevance
“…Basal feet appeared to be enlarged and oriented parallel to commissural growth cones (Figure 13(c)). This was in line with previous reports in the chicken and mouse embryos (Campbell & Peterson, 1993;Ducuing et al, 2020;Yaginuma et al, 1991;Yoshioka & Tanaka, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…Basal feet appeared to be enlarged and oriented parallel to commissural growth cones (Figure 13(c)). This was in line with previous reports in the chicken and mouse embryos (Campbell & Peterson, 1993;Ducuing et al, 2020;Yaginuma et al, 1991;Yoshioka & Tanaka, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…However, the work presented in this article demonstrates that Slit-FL and Slit-N have dramatically different activities in vivo . The key to these findings was the identification of Tok as the Slit protease, allowing in vivo genetic manipulation of Slit fragments to uncover the independent biological function of Slit-N. Our results complement the few studies in which Slit-FL and Slit-N have been observed to have distinct activities ( Gohrig et al, 2014 ; Nguyen Ba-Charvet et al, 2001 ; Wang et al, 1999 ) as well as those that have attributed activities to a specific Slit fragment ( Wright et al, 2012 ; Ducuing et al, 2020 preprint; Caipo et al, 2020 ). As Slit cleavage and Tok family proteases are evolutionarily conserved ( Brose et al, 1999 ; Hopkins et al, 2007 ), it seems highly likely that processing of Slits by BMP-1/Tolloid family proteases will diversify the biological output of Slit signaling in many different systems.…”
Section: Discussionsupporting
confidence: 64%